The Role of Sphingolipids in Allergic Disorders - Díaz-Perales, Araceli; Escribese, Maria M.; Garrido-Arandia, María; Obeso, David; Izquierdo-Alvarez, Elena; Tome-Amat, Jaime; Barber, Domingo (Frontiers in Allergy, 2021)
Allergy is defined as a complex chronic inflammatory condition in which genetic and environmental factors are implicated. Sphingolipids are involved in multiple biological functions, from cell membrane components to critical signaling molecules. To date, sphingolipids have been studied in different human pathologies such as neurological disorders, cancer, autoimmunity, and infections. Sphingolipid metabolites, in particular, ceramide and sphingosine-1-phosphate (S1P), regulate a diverse range of cellular processes that are important in immunity and inflammation. Moreover, variations in the sphingolipid concentrations have been strongly associated with allergic diseases. This review will focus on the role of sphingolipids in the development of allergic sensitization and allergic inflammation through the activation of immune cells resident in tissues, as well as their role in barrier remodeling and anaphylaxis. The knowledge gained in this emerging field will help to develop new therapeutic options for allergic disorders.